Enhanced gamification in study skills / Ini Imaina Abdullah … [et al.] - Abdullah, Ini Imaina; Jamal, Nur Faezah; Abdul Rahman, Anisah; Abdul Razak, Samsiah; Talkis, Azizah (UiTM Cawangan Melaka Kampus Jasin, 2021)
Educators are facing challenges when teaching through face to face cannot be implemented due to the unforeseen circumstances of the current pandemic outbreak. In order to ensure learning delivery is achieved, they have to shift to online distance learning method to teach the students. This raises concerns in regards to students’ performance and engagement, hence gamification is introduced in Study Skills to allow them to engage with the learning materials in a new and dynamic way and essentially improve their performance. Gamification can be considered as one of the technologies used to support the traditional ways of teaching and learning. This study aims to apply the gamification techniques in Study Skills course. Kahoot, Quizizz and QuizWhizzer are the tools used in creating the gamified learning activities. A questionnaire was conducted to gather responses from the students after the completion of the course.